PENINGKATAN KUALITAS MOTORIK ANAK MELALUI PENDIDIKAN ANAK USIA DINI BERBASIS ALAT PERMAINAN EDUKATIF DI POS PAUD PELANGI KELURAHAN MERGOSONO KECAMATAN KEDUNGKANDANG MALANG - Baroroh Lestari; Pudji Herijanto; Ellyn Eka Wahyu; Heru Utomo; Diana Eka Poernamawati (Publisher UPT P2M Politeknik Negeri Malang, 2019)
The target in this activity is Pos PAUD Mergosono, Kedungkandang District, Malang. Community dedication activities in PAUD Pelangi in Mergosono Sub-District, Kedungkandang District, Malang City are very beneficial for partners, especially in improving the quality of learning. Thus, teaching and learning activities will be more interesting and children will have the opportunity to develop their potential, which in turn will also improve children's motor skills. The activities that have been carried out in community dedication are aimed at increasing APE equipment and lockers to store them. While for managers, training on management and administration of PAUD managers is given. Based on the results of the implementation of the service that has been done can ask for advice: 1) The existence of follow-up activities that contain special training so that it can improve the ability of teachers to carry out teaching and learning. 2) APE procurement needs to be done to improve children's motor skills.